KEMAHIRAN KEUSAHAWANAN DALAM KALANGAN PELAJAR TAHUN AKHIR (FPTV) DI UTHM - Subramaniam, Tamil Selvan; Ab Majid, Nur Fazilah; Ariffin, Arihasnida; Hamzah, Norhasyimah; Rubani, Siti Kamariah (Online Journal for TVET Practitioners, 2018)
Entrepreneurship skills involve the ability to explore opportunities and develop risk awareness, creativity and innovation in business related activities. The problem of the study is that there is little finding about the level of entrepreneurial skills applied through teaching and learning activities and caused the increasing rate of unemployment graduates. This research aims to identify the extent of entrepreneurial skills among the final year students of the Faculty of Technical and Vocational Education (FPTV) at UTHM. Quantitative research used by survey method and questionnaires to collect data. The respondents involved from 144 fourth year students which is a final year of Bachelor of Vocational Education in FPTV,UTHM. The data were analyzed using the Statistical Package of Social Science (SPSS) version 21.0 and interpreted in the form of mean and standard deviation. The results showed that students have medium acceptance against three aspects which are in terms of, identifying the ability of final year students (FPTV) to take business opportunities through learning and teaching activities at UTHM, identifying the ability to design business planning and identify the ability to work on their own in the field of entrepreneurship as a career opportunity. The contribution of the research can be used as a benchmark for instructors in planning the best strategies to enhance entrepreneurship levels through teaching and learning activities. Questionnaire instruments can also be used for research that almost the same as references for future research.